Development of functional cotton fabric by simultaneous dyeing and finishing with a novel bioactive reactive dye. (3rd January 2023) - Nosheen, Anum; Ashraf, Munir; Hussain, Muhammad Tahir; Aziz, Humera; Tahir, Muhammad Farrukh; Akram, Saba
Abstract : Bioactive textiles garnered considerable attention during the COVID-19 pandemic owing to their antimicrobial properties. Abstract : Bioactive textiles garnered considerable attention during the COVID-19 pandemic owing to their antimicrobial properties. However, the fabrication and utilization of bioactive textiles have had a toxic impact on the environment due to the leaching of bioactive agents during laundering. In this study, a novel functional bioactive reactive dye was synthesized using an antibacterial agent covalently linked to a triazine reactive group for the simultaneous dyeing and finishing of cotton fabric. The molecular structure of the synthesized dye was characterized using FTIR, 1 H-NMR, 13 C-NMR, MS, and UV-vis spectroscopy. The dye was applied to the cotton fabric using the exhaust dyeing method. The antibacterial efficacy of the powder dye and dyed fabric against Staphylococcus aureus and Escherichia coli was estimated according to standard test protocols. The color strength ( K / S ), colorimetric data ( L *, a *, b *, C*, H *) measurement, ultraviolet protection, and colorfastness properties of the dyed fabric were also evaluated. The synthesized powder dye revealed an outstanding antibacterial activity and killed 99.99% of bacteria ( E. coli and S. aureus ). The dyed fabric showed excellent antibacterial activity before washing as well as after 20 industrial laundry cycles and showed that there was no significant reduction in antibacterial activity, establishing non-leaching of the antibacterial agent into the environment. The dyed fabrics before and after washing showed excellent ultraviolet protection values (>50), better dye fixation, and fastness properties. The current study has established a sustainable process to develop bioactive textiles that do not leach bioactive agent into the environment.